ChemInform Abstract: Synthesis of 5‐Amino‐3, 3‐dimethyl‐7‐phenyl‐3H‐[1, 2]oxathiolo [4, 3‐b]pyridine‐6‐carbonitrile 1, 1‐Dioxides. Issue 11 (March 2015) - Chioua, Mourad; Samadi, Abdelouahid; Postel, Denis; Balzarini, Jan; Marco‐Contelles, Jose
Abstract via Michael reaction of dioxides (I) with malononitriles (II) using piperidine as catalyst